Whole‐exome DNA sequence analysis of Brca2‐ and Trp53‐deficient mouse mammary gland tumours. Issue 2 (2nd April 2015) - Francis, Jeffrey C; Melchor, Lorenzo; Campbell, James; Kendrick, Howard; Wei, Wenbin; Armisen‐Garrido, Javier; Assiotis, Ioannis; Chen, Lina; Kozarewa, Iwanka; Fenwick, Kerry; Swain, Amanda; Smalley, Matthew J; et al.
Abstract Germline mutations in the tumour suppressor BRCA2 predispose to breast, ovarian and a number of other human cancers. Brca2‐deficient mouse models are used for preclinical studies but the pattern of genomic alterations in these tumours has not yet been described in detail. We have performed whole‐exome DNA sequencing analysis of mouse mammary tumours from Blg–Cre Brca2f/f Trp53f/f animals, a model of BRCA2‐deficient human cancer. We also used the sequencing data to estimate DNA copy number alterations in these tumours and identified a recurrent copy number gain in Met, which has been found amplified in other mouse mammary cancer models. Through a comparative genomic analysis, we identified several mouse Blg–Cre Brca2f/f Trp53f/f mammary tumour somatic mutations in genes that are also mutated in human cancer, but few of these genes have been found frequently mutated in human breast cancer. A more detailed analysis of these somatic mutations revealed a set of genes that are mutated in human BRCA2 mutant breast and ovarian tumours and that are also mutated in mouse Brca2‐null, Trp53‐null mammary tumours. Finally, a DNA deletion surrounded by microhomology signature found in human BRCA1/2‐deficient cancers was not common in the genome of these mouse tumours. Although a useful model, there are some differences in the genomic landscape of tumours arising in Blg–Cre Brca2f/f Trp53f/f mice compared to human BRCA‐mutated breast cancers. Therefore, this needs to be taken into account in the use of this model. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.